Studi Literatur Pengaruh Musik Instrumentalterhadap Kondisi Burnout Syndrome Pada Dosen Perguruan Tinggi - Florensia Susanto, Magdalena; Retno Suminar, Dewi (CV RIFAINSTITUT, 2022)
Based on education level, several studies have found that the higher the level of education, the higher the burnout rate. This is possible because someone with a higher level of education, works with greater responsibility and a high level of stress. This study aims to obtain an overview of the influence of instrumental music and work stress on the Burnout Syndrome condition of university lecturers, both public and private. This research uses literature study methods on electronic databases, such as: Educational Administration Quarterly Journal, Research in Education, Active Learning in Higher Education SAGE Journals, Indonesian Psychology Journal, Undip Psychology Journal, Theoretical and Applied Psychology Journal, Psychology Science Journal, Psychology Journal Scientific, Interventional Psychology Journal, Psychological Research and Thought Journal, Mulawarman University Psychostudia Journal, UMA Psychology Masters Journal, Psychopoly Tan from 2003-2019. Several studies discuss burnout in terms of other factors, social support, self-efficacy, self-concept, self-regulation, gratitude, professional identity, life pressure, consciousness personality dimensions, role ambiguity, and workload.